Legislation, Regulation and Litigation: Demand for U.S. Legal Services in Historical Perspective - Ariell Reshef; Cailin Slattery (CESifo GmbH, 2025)
The employment share of legal services in the U.S. more than doubled during 1970–1990, in stark contrast to stability during 1850–1970 and after 1990. The relative wage of lawyers and law firm partners also doubled between 1970 and 1990. We argue that this demand shift was driven by important legislative and regulatory events, starting in the mid-1960s and lasting throughout the 1980s. These changes increased the scope of the law and uncertainty over legal outcomes. Consistent with this, we find that employment and compensation of lawyers are tightly correlated with federal regulation, fee-shifting statues and civil litigation, over a period of 100 years. These findings are supported by state-level and individual-level analysis. Other factors, e.g., changes in lawyers' quality, industrial composition and technology are not important determinants of the demand shift. We calculate that 40% of payments to legal services in 1990 are in excess of what they would have been had their relative income remained at 1970 levels. This represents an excess cost of 75 billion dollars in 2024 alone.
Keywords: J20; J30; N30; K00; 330; legal services; lawyers; legislation; deregulation; litigation; labor demand